Morphometric measurements of pearl shell shells Pinctada margaritifera for aquarium cultivation - Torang J. P Silalahi; Cyska Lumenta (Masyarakat Moluska Indonesia, 2022)
The pearl oyster Pinctada margaritifera or the black-lipped oyster is one of the important species used in the pearl industry. The availability of natural pearl oyster seeds is limited, while exploitation is increasing. The purpose of this field work practice is to measure and observe the morphometric comparisons of Arakan, Mantehage Bango and Talengen waters. The time for the implementation of the field work practice begins in January 2020. This field work practice is carried out at the Mamuaya family work laboratory, Malalayang. The method used in this field work practice is a method of direct observation of the object being measured morphometrically. The morphometric measurements were processed using Microsoft Excel. Morphometric measurements of the shells of P. margaritifera were carried out by measuring the dimensions of the shells, namely shell length, shell height, shell hinge length and shell thickness. This shell measurement uses a digital vernier caliper caliper to make it easier to measure with an accuracy of 0.01 mm.Changes in the morphometric character of P. margaritifera shellfish based on different locations indicated that there were different environmental factors. This can be seen from the variation in size after the shell measurement process was carried out from three different locations. The location of Arakan waters has shellfish morphometric characters which tend to be larger than the samples of P. margaritifera in the waters of Mantehage Bango and Talengen. The shells of P. clams from Arakan waters have a shell size with a height of 169.77 mm in length, 183.78 in height, 113.11 in hinge length and 55.16 mm in thickness. The shell morphometric characters of P. margaritifera from Talengen waters varied with shell length 105.34 mm, shell height 116.34 mm, hinge length 66.41 mm, shell thickness 36.2 mm. The highest shell morphometric characters of P. margaritifera in Mantehage waters were obtained with a shell length of 111.35 mm, shell height 112.5 mm, shell hinge length 57.89 mm, and shell thickness 59.21 mm.